Introduction to AutoCAD 2024 : a modern perspective - Richard, Paul (Paul Fritz) (Pearson, 2021)
Introduction to AutoCAD 2024 addresses advances in technology and introduces students to 2-dimensional drawing skills and commands using the 2024 release of AutoCAD. Straightforward explanations focus on actual drawing procedures, and illustrations show what to expect on the computer screen. It continuously builds on concepts covered in previous chapters, contains exercises combined with in-text notes, and offers examples that provide the how and why of AutoCAD fundamentals. Projects are included at the end of each chapter and provide hands-on experience creating various types of mechanical, architectural, civil, and electrical drawings. This text is appropriate for introductory and intermediate AutoCAD courses.